Investigating the Presence and Levels of Some Selected Chemical Parameters in Borehole Water of Ga-Matlala in Limpopo Province, South Africa: Determining the Potential Risks - C.J. Mabe; D.M. Molefe; S.S. Gololo (SAGE Publishing, 2024)
The safety of borehole water is highly questionable, yet most people in the African continent still depend on borehole water as the primary source for everyday use. To investigate the potential health risk of borehole water on the community, this study analyzed the presence and levels of various chemical parameters in borehole water of Ga-Matlala area in Limpopo province, South Africa. Twenty-four water samples were collected from selected eight villages of ga-Matlala during both the dry and rainy seasons. Techniques such as UV/vis spectrophotometric method, EDTA titrimetric method, Cl - argentometric method and FAAS were used to determine fluoride, nitrate, hardness, calcium, chloride ion and magnesium. In the rainy season, hardness ranged from 146.10 to 1136.49 mg/L, calcium ranged between 252.54 to 448.2 mg/L. In the dry season, hardness ranged between 157.69 to 1003.80 mg/L, calcium concentration ranged between 183.43 and 385.37 mg/L. The recommended limits set by regulatory authorities were exceeded in both seasons. Fewer samples recorded chloride concentration ⩾ 100 mg/L in both seasons. Magnesium concentrations were between 0.72 and 1.35 mg/L in both seasons. Fluoride concentration exceeded the maximum permissible level by regulatory bodies in most samples. In the rainy season, the lowest concentration was 1.94 mg/L, and a maximum was 3.22 mg/L. The nitrate concentration in both seasons was around 0.3 mg/L. Magnesium concentrations were within the acceptable levels. The elevated levels of chemicals in borehole may lead to dental fluorosis, risk of kidney stones and cancer in human beings. It is therefore recommended that risk awareness action should be undertaken, and treatment interventions should be considered.